Fencing In and Out: Israel's Separation Wall and the Whitewashing of State Violence - Sa’ar, Amalia; Aharoni, Sarai B.; Lewin, Alisa C. (Review of International American Studies, 2018)
Amalia Sa’ar (University of Haifa, Israel) Sarai Aharoni (Ben-Gurion University, Israel) Alisa Lewin (University of Haifa, Israel) Fencing In and Out: Israel's Separation Wall and the Whitewashing of State Violence Abstract: This essay uses the case of Israel's Separation Wall to address the role of walls in the articulation of security, violence, vulnerability, and danger. In Israel, "security" refers exclusively to the Jewish citizens, whether they are fenced in (residing within the Green Line) or outside it (such as West Bank settlers). For the Palestinians, by contrast, the wall is yet another instrument of structural and symbolic violence. While Israeli Jews are vaguely aware of "the occupation," they largely remain blissfully unaware of the violent under-side of everyday civil security, which the wall represents. Tracing the ways in which Jewish citizens living inside the Green Line experience and accommodate the wall, this essay analyzes its role in whitewashing state violence and in the ongoing construction of subject positions with respect to the security-violence complex. Keywords: security, state violence, gated communities, misrecognition, the political, Israel-Palestine, Separation Wall